Baroclinic effects on the distribution of tropical cyclone eye subsidence - Schubert, Wayne H.; Taft, Richard K.; Slocum, Christopher J. (Frontiers in Earth Science, 2022)
Solutions of the secondary (transverse) circulation equation for an axisymmetric, gradient balanced vortex are used to better understand the distribution of subsidence in the eye of a tropical cyclone. This secondary circulation equation is derived using both the physical radius coordinate r and the potential radius coordinate R. In the R-coordinate version, baroclinic effects are implicit in the coordinate transformation and are recovered in the final step of transforming the solution for the streamfunction Ψ back from R-space to r-space. Two types of elliptic problems for Ψ are formulated: (1) the full secondary circulation problem, which is formulated on 0 ≤ R < ∞, with the diabatic forcing due to eyewall convection appearing on the right hand side of the elliptic equation; (2) the restricted secondary circulation problem, which is formulated on 0 ≤ R ≤ Rew, where the constant Rew is the potential radius of the eyewall, with no diabatic forcing but with the streamfunction specified along R = Rew. The restricted secondary circulation problem can be solved semi-analytically for the case of vertically sheared, Rankine vortex cores. The solutions identify the conditions under which large values of radial and vertical advection of θ are located in the lower troposphere at the outer edge of the eye, thereby producing a warm-ring thermal structure.